2022
DOI: 10.18549/pharmpract.2022.1.2611
|View full text |Cite
|
Sign up to set email alerts
|

The impact of synchronous hybrid instruction on students’ engagement in a pharmacotherapy course

Abstract: Background: Synchronous hybrid instruction offers flexible learning opportunities by allowing a portion of students to attend class sessions on campus while simultaneously allowing the remaining students to attend remotely. Although such flexibility may offer a number of advantages for pharmacy students, one area of concern is whether online participation options within synchronous hybrid courses can promote similar levels of engagement as courses that are designed entirely for face-to-face (FTF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…One of the first issues that the research has identified is the unreliability of the internet network. The learning process is interrupted because of the poor internet connection that happened during class session (Anable et al, 2022; Pham & Pham, 2022; Radhyi & Usman, 2022; Doghonadze, 2021; Palmer et al, 2022). It serves no purpose to have an HLE that requires participants to access the internet from anywhere in the world unless there is a good internet connection.…”
Section: Discussionmentioning
confidence: 99%
“…One of the first issues that the research has identified is the unreliability of the internet network. The learning process is interrupted because of the poor internet connection that happened during class session (Anable et al, 2022; Pham & Pham, 2022; Radhyi & Usman, 2022; Doghonadze, 2021; Palmer et al, 2022). It serves no purpose to have an HLE that requires participants to access the internet from anywhere in the world unless there is a good internet connection.…”
Section: Discussionmentioning
confidence: 99%
“…"Zoom fatigue" is the exhaustion that comes from engaging in videoconferences for multiple hours a day (Bailenson, 2021). Factors contributing to Zoom fatigue with online learning include an increase in distractions and multitasking, technology not working, lack of nonverbal communication, intermittent feedback from other participants, inability to see facial cues due to cameras being turned off, and constantly viewing oneself (Bailenson, 2021;Palmer et al, 2022;Peper et al, 2021). Therefore, online synchronous sessions require "an increased effort to maintain students' attention" (Fuller et al, 2021, p. 107) and more cognitive efforts to engage learners (Fauville et al, 2021).…”
Section: Comparisons Of Two Teaching Approaches For Online Rdm Instru...mentioning
confidence: 99%
“…Research supports collaborative learning, such as collaborative note-taking, as a way to effectively engage students in classroom learning (Costley et al, 2022;Igel & Urquhart, 2012). For example, during online instruction, the use of chat, breakout rooms, and changing up classroom activities have been shown to increase students' engagement (Palmer et al, 2022;Toney et al, 2021). Yao et al (2020) also showed that interactive teaching methods had a greater impact on student outcomes in the synchronous online teaching context during the COVID-19 pandemic, compared to students who only received online video modules.…”
Section: Comparisons Of Two Teaching Approaches For Online Rdm Instru...mentioning
confidence: 99%
“…While the ones who want to see the teacher in person may come to school to join the face-to-face instruction. In other words, hybrid learning provides flexibility for students (Detyna et al, 2022;Palmer et al, 2022). In addition, conducting synchronous hybrid learning could decrease the teachers' absence.…”
Section: Figure 1 Learning Responsibilitymentioning
confidence: 99%
“…Another reason the hybrid was preferred was the flexibility of learning around their busy schedules while maintaining contact with the lecturer. They can also set the time and freedom to choose whether to take classes face-to-face or online (Palmer et al, 2022). This is also an effort to get around the limitations that we experience in this post-COVID-19 period.…”
Section: Figure 4 Learning Style and Needsmentioning
confidence: 99%